RANCANG BANGUN MESIN PEMBERSIH GULMA SEMI OTOMATIS (Universitas Islam 45 Bekasi, Fakultas Teknik, Jurusan Teknik Mesin, 2021)
Farmers in Indonesia currently still use traditional tools to cut weeds because they are cheaper. However, it has many drawbacks, including taking a long time and a lot of manpower. Therefore this research is to create a weed cleaning machine with a cheaper and more efficient cost. In the research, the design of the semi-automatic weed cleaning machine was carried out and after that the performance testing of the tool was carried out. From the test, it was concluded that in this study, a semi-automatic weed cleaning machine has been successfully built with an engine power of 401.9 W or 0.538 HP, 6.4 Nm of torque and gasoline. Semi Automatic weed cutting machine capable of cutting weeds for an area of 1 hectare takes an average of 34.7 hours with a manufacturing cost of Rp.2.225.000.